A hybrid systematic review and bibliometric analysis of character education in science and social studies - Fadilla Aisah Nurikhsani; Wasino Wasino; Eko Handoyo; Sarwi Sarwi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Character education is increasingly crucial amid growing social complexity. However, its integration within science and social studies remains fragmented. This study aims to map research trends, identify dominant character values, and examine key gaps in this field. A hybrid approach combining a systematic literature review and bibliometric analysis was applied to 131 Scopus-indexed articles (2016–2025). The findings reveal a growing body of research with a fragmented yet interconnected intellectual structure. Five categories of character values were identified, with social–civic and moral–ethical values as the most dominant, followed by scientific, environmental, and social–emotional values. Six main pedagogical approaches were integrated learning, project-based learning, and citizenship-based approaches. Key gaps include the absence of an integrated conceptual framework, limited use of experimental and longitudinal designs, and insufficient development of context-sensitive character assessment tools. These findings highlight the need for more integrated models, rigorous research designs, and practical strategies to support effective character education in science and social studies.